Biomaterial containing magnetotactic bacteria as well as preparation method and application of biomaterial
By depositing nutrient layers and tannin-Fe3+ layers on the carrier, the magnetotropic bacteria are fixed, and the problems of low uranium removal efficiency and uranium re-release in iron-containing environments are solved, achieving efficient and stable uranium wastewater treatment.
Patent Information
- Application Number
- CN202510027467.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-08
- Publication Date
- 2025-04-04
AI Technical Summary
Prior art When treating uranium-containing wastewater, the presence of iron ions will affect the adsorption efficiency and stability of uranium, resulting in the possibility that uranium elements may be released into the environment again.
Using biomaterials containing magnetotaxis, the magnetotaxis are fixed by depositing nutrient layers and tannin-Fe3+ layers on the carrier, and the bacteria are protected by Fe3+ to improve the removal efficiency and stability of uranium.
The removal efficiency of uranium in wastewater is significantly improved, the risk of re-release of uranium elements is reduced, and the removal efficiency decays slowly when the uranium concentration in wastewater increases.
Smart Images

Figure CN119752728A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of soil and groundwater pollution control, and in particular to a biological material containing magnetotactic bacteria, and a preparation method and application thereof. Background Art
[0002] The treatment of uranium (U)-containing wastewater is an important topic in the field of nuclear industry and environmental protection. With the continuous expansion of nuclear energy utilization, uranium-containing wastewater, which mainly comes from uranium mining, smelting, nuclear fuel production and other links, has become the key to protecting the environment and human health. The uranium in uranium-containing wastewater mainly exists in the form of U(VI), which has high mobility and bioaccumulation, and is chemically toxic and radioactively toxic to the human body. If it is directly discharged without proper treatment, it will pose a major threat to the ecological environment and public health.
[0003] At present, the treatment technologies for uranium-containing wastewater mainly include chemical precipitation, ion exchange, adsorption, membrane separation and biological treatment. The chemical precipitation method adds chemical substances to make the uranium element form insoluble compound precipitation; the ion exchange method uses ion exchange resin to adsorb uranium ions; the adsorption method uses porous adsorbents to quickly adsorb uranium; the biological method uses microorganisms to reduce soluble and easily mobile U(VI) to non-mobile U(IV). The biological method for treating uranium-containing wastewater has the advantages of being environmentally friendly, cost-effective, efficient and safe.
[0004] During the uranium mining process, a noteworthy phenomenon is that iron ore often exists with uranium ore. This symbiotic relationship leads to the release of iron in different valence states, namely ferrous ions (Fe²⁺) and ferric ions (Fe³⁺), during the uranium mining and subsequent processing stages, especially during the acid leaching process. These iron ions will then exist in the wastewater generated by uranium mining and become part of the wastewater composition.
[0005] Therefore, the presence of Fe ions (including Fe²⁺ and Fe³⁺) can often be detected in uranium-containing wastewater. The presence of these iron ions in wastewater has a certain impact on the treatment and disposal of uranium. On the one hand, Fe²⁺ and Fe³⁺ are positively charged cations like the hexavalent form of uranium U(VI) (usually in the form of uranyl ions UO2²⁺). During wastewater treatment, when adsorbents are used to remove these cations, Fe²⁺, Fe³⁺ and UO2²⁺ compete with each other for adsorption sites on the surface of the adsorbent. This competition may lead to a decrease in the adsorption efficiency of the adsorbent for uranium because the adsorption sites may be occupied by a large number of iron ions.
[0006] On the other hand, Fe³⁺ is also oxidizing. It may react with the tetravalent form of uranium, U(IV), to oxidize the less mobile U(IV) into the more mobile U(VI). This oxidation may cause the relatively stable U(IV) that is not easily released into the environment to be released into the wastewater again, thereby increasing the potential risk of uranium to the environment. Therefore, when treating uranium-containing wastewater, it is necessary to fully consider the presence of iron ions and their possible impact.
[0007] Magnetotactic bacteria can simultaneously mineralize U(VI) and iron ions (Fe 2+ and Fe 3+ ), generating a stable uranium-iron mixture and a uranium-phosphorus mixture. The generated products will fall off automatically and are easy to recycle, solving the problem of removing U(VI) in an iron-containing environment. The special mineralization function of magnetotactic bacteria can mineralize U(VI) in an iron-containing environment. Since U(VI) is not fixed by reduction, the problem of uranium being oxidized and released will not occur.
[0008] However, the direct use of magnetotactic bacteria or the simple loading of magnetotactic bacteria on a carrier for uranium wastewater treatment will result in a low removal efficiency of uranium in the wastewater, and the removal efficiency will decay rapidly with the increase of uranium concentration in the wastewater. Summary of the invention
[0009] The object of the present invention is to provide a biomaterial containing magnetotactic bacteria, which has high removal efficiency for U(VI) in an iron-containing environment and slow decay with increasing uranium concentration in wastewater; another object of the present invention is to provide a method for preparing the biomaterial containing magnetotactic bacteria; another object of the present invention is to provide an application method of the biomaterial containing magnetotactic bacteria.
[0010] The present invention discloses a biological material containing magnetotactic bacteria, comprising:
[0011] Magnetotactic bacteria, wherein the magnetotactic bacteria is Magnetospirillum gryphiswaldense DSM6361;
[0012] A carrier for fixing the magnetotactic bacteria;
[0013] A nutrient salt layer is deposited on the surface of the carrier to provide nutrients for the magnetotactic bacteria;
[0014] Tannic acid-Fe 3+ layer, attached to the surface of the nutrient salt layer.
[0015] The nutrient salt layer provides essential nutrients for the growth and reproduction of magnetotactic bacteria.
[0016] The carrier is mainly used to deposit nutrient salt layers, tannic acid-Fe 3+To layer and fix magnetotactic bacteria, the carrier can be ceramic filler, activated carbon, zeolite, volcanic rock, fiber material, sand, gravel, glass, carbon fiber, etc.
[0017] Tannic acid-Fe 3+ Fe 3+ Positively charged, on the one hand, it can adsorb negatively charged magnetotactic bacteria (the phospholipid structure of the bacterial cell membrane is negatively charged), on the other hand, when the U(VI) content in the wastewater is too high and Fe 3+ When the content of tannic acid-Fe is insufficient, 3+ Fe in the layer 3+ Can supplement insufficient Fe 3+ , enters the body of magnetotactic bacteria together with U(VI), preventing excessive U(VI) from eroding the cells of magnetotactic bacteria and protecting them. Tannic acid has bactericidal function, generally combining with proteins, polysaccharides or lipids on the surface of bacteria, thereby changing the bacterial structure and making the bacteria lose the ability to grow and reproduce. 3+ Under the protection of magnetotactic bacteria, it can be protected from the invasion of tannic acid. Therefore, tannic acid will not affect the growth of magnetotactic bacteria but can inhibit the growth of other bacteria.
[0018] Furthermore, the carrier includes hydrophilic carbon fibers.
[0019] Using hydrophilic carbon fibers as carriers has the advantages of enhanced microbial attachment ability, easy regeneration, high specific surface area, good mechanical properties, and excellent chemical stability.
[0020] The present invention also discloses a method for preparing a biological material containing magnetotactic bacteria, comprising the following steps:
[0021] S1 acid washing: the carrier is soaked in an acid solution for washing, washed with an alkaline aqueous solution until neutral, then washed with water, and dried;
[0022] S2 deposition of nutrient salt layer: soak the cleaned carrier in nutrient salt liquid, sterilize, soak for 20-28 hours, take out, wash with water, and dry;
[0023] S3 Tannic Acid-Fe 3+ Layer self-assembly: Deposition of nutrient carriers, water, tannic acid and Fe 3+ The solutions were mixed, the pH of the mixed solution was adjusted to 6.5-7.5, ultrasonically reacted for 10-20 min, washed with water, and dried;
[0024] S4 loading magnetotactic bacteria: the carrier treated in step S3 is mixed with a culture medium containing magnetotactic bacteria Magnetospirillum gryphiswaldense DSM6361, and cultured to obtain the biomaterial containing magnetotactic bacteria as described above.
[0025] Impurities on the carrier surface are removed by pickling to increase the porosity of the carrier.
[0026] Furthermore, in step S1, the acid solution is a 2-3 wt% nitric acid aqueous solution; the cleaning is ultrasonic cleaning for 20-30 min; and the alkaline aqueous solution is a 2-8 wt% sodium hydroxide aqueous solution.
[0027] Furthermore, in step S2, the nutrient salts include: sodium lactate, ammonium chloride, dipotassium hydrogen phosphate, magnesium sulfate, yeast powder, sodium thioglycolate, and a mixture of mineral elements; the mixture of mineral elements includes: nitrilotriacetic acid, magnesium sulfate, manganese sulfate, sodium chloride, ferrous sulfate, cobalt sulfate, calcium chloride, zinc sulfate, copper sulfate, potassium aluminum sulfate, boric acid, sodium molybdate, nickel chloride, and sodium selenite.
[0028] Furthermore, the nutrient salts include: sodium lactate (content 60wt%) 3-7g / L, ammonium chloride 0.5-1.2g / L, dipotassium hydrogen phosphate 0.5-1.5g / L, magnesium sulfate heptahydrate 0.1-0.3g / L, yeast powder 0.1-0.3g / L, sodium thioglycolate 0.05-0.15g / L, mineral element mixture 0.5-2mL / L, pH 6.5-7; wherein the mineral element mixture includes: nitrilotriacetic acid 10-20g / L, magnesium sulfate 25-35g / L , manganese sulfate 3-8g / L, sodium chloride 8-12g / L, ferrous sulfate 0.8-1.5g / L, cobalt sulfate 1.5-2.0g / L, calcium chloride 0.5-1.5g / L, zinc sulfate 1.5-2.0g / L, copper sulfate 0.05-0.15g / L, potassium aluminum sulfate 0.1-0.5g / L, boric acid 0.05-0.15g / L, sodium molybdate 0.05-0.15g / L, nickel chloride 0.1-0.5g / L, sodium selenite 0.001-0.005g / L.
[0029] Furthermore, in step S2, the sterilization is performed at a temperature of 115-125° C. for 20-40 min.
[0030] The pH of the mixture is controlled at 6.5-7.5. Tannic acid contains abundant hydroxyl groups (-OH) with negative charge, which will react with Fe 3+ Complexation reaction occurs, and the network unit structure formed is as follows Figure 1 As shown, the self-assembled network structure is loaded on the surface of the carrier; at the same time, controlling the pH within this range will not affect the growth and reproduction of magnetotactic bacteria.
[0031] Furthermore, in step S3, the mass of the carrier: the volume of water: the mass of tannic acid: Fe 3+ The mass ratio is 4-6 g:500 mL:0.2-0.3 g:3-5 mg.
[0032] Furthermore, in step S4, the culture medium containing the magnetotactic bacteria Magnetospirillum gryphiswaldense DSM6361 is inoculated with 3-7 (v / v)% of 10 6 -10 7 / mL of seed solution; culture at 20-35℃, 80-140 rpm / min for 20-28 h.
[0033] The invention also discloses a uranium wastewater removal device, comprising a biological material containing magnetotactic bacteria prepared by the preparation method described above.
[0034] Furthermore, a uranium wastewater removal device comprises:
[0035] The container has an upper end and a lower end, the end close to the ground is the upper end, and the end away from the ground is the lower end; the container is enclosed to form a containing space;
[0036] A biological material containing magnetotactic bacteria is located in the container and divides the containing space into two vertical parts;
[0037] A supporting net is located on both sides of the biological material containing magnetotactic bacteria; the supporting net divides the containing space into two parts by the biological material containing magnetotactic bacteria;
[0038] A water inlet is provided on one side of the part into which the accommodation space is divided, close to the lower end;
[0039] The water outlet is arranged on one side close to the upper end of the other part into which the accommodating space is divided.
[0040] The invention discloses a biological material containing magnetotactic bacteria, wherein a nutrient salt layer and tannic acid-Fe are deposited on a carrier. 3+ Layer, the deposited nutrient salt layer provides nutrients for the growth and reproduction of magnetotactic bacteria; tannic acid-Fe 3+ The layer can not only adsorb and protect magnetotactic bacteria, but also Fe 3+ Provide Fe when insufficient 3+ It is used by magnetotactic bacteria and inhibits the growth of other bacteria. 3+ The uranium removal efficiency of the wastewater can be improved by depositing the uranium on the carrier of the layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 The Fe 3+ The network unit structure diagram formed by complexation reaction with tannic acid;
[0042] Figure 2This is a scanning electron microscope image of the carbon fiber used in Example 1 of the present invention;
[0043] Figure 3 Schematic diagram of the steps of acid washing of carbon fiber and deposition of nutrient salt layer in Example 1 of the present invention;
[0044] Figure 4 The carbon fiber of Example 1 of the present invention is self-assembled to form tannic acid-Fe after nutrient salt is deposited 3+ Schematic diagram of the layers and steps for loading magnetotactic bacteria;
[0045] Figure 5 This is a schematic diagram of the principle of mineralization of U(VI) by the biomaterial containing magnetotactic bacteria prepared in Example 1 of the present invention;
[0046] Figure 6 It is a schematic diagram of the structure of the uranium wastewater removal device in the present invention;
[0047] Figure 7 is a cross-sectional view of a uranium wastewater removal device in the present invention;
[0048] Figure 8 The biological material containing magnetotactic bacteria in Example 2 of the present invention is used to treat the biological material containing U(VI), Fe 2+ and Fe 3+ Scanning lens images of wastewater before (part a) and after treatment (part b);
[0049] Fig. 9 The present invention is the embodiment 2 of the present invention to treat the U (VI), Fe 2+ and Fe 3+ Transmission electron microscope image of the product after wastewater treatment;
[0050] Fig.10 The present invention is the embodiment 2 of the present invention to treat the U (VI), Fe 2+ and Fe 3+ Elemental analysis results of the products after wastewater treatment;
[0051] Fig.11 The present invention is the embodiment 2 of the present invention to treat the U (VI), Fe 2+ and Fe 3+ Schematic diagram of the concentration of each element in the wastewater before and after treatment;
[0052] Fig.12 The biological material containing magnetotactic bacteria in Example 3 of the present invention is used to treat the biological material containing U(VI), Fe 2+ and Fe 3+ Scanning lens images of wastewater before (part a) and after treatment (part b);
[0053] Fig.13 The present invention is the embodiment 3 of the treatment of U (VI), Fe2+ and Fe 3+ Transmission electron microscope image of the product after wastewater treatment;
[0054] Fig.14 The present invention is the embodiment 3 of the treatment of U (VI), Fe 2+ and Fe 3+ Elemental analysis results of the products after wastewater treatment;
[0055] Fig.15 The present invention is the embodiment 3 of the treatment of U (VI), Fe 2+ and Fe 3+ Schematic diagram of the concentration of each element in the wastewater before and after treatment;
[0056] Fig.16 The biological material containing magnetotactic bacteria in Example 4 of the present invention is used to treat the biological material containing U(VI), Fe 2+ and Fe 3+ Scanning lens images of wastewater before (part a) and after treatment (part b);
[0057] Fig.17 The present invention is the embodiment 4 of the treatment of U (VI), Fe 2+ and Fe 3+ Transmission electron microscope image of the product after wastewater treatment;
[0058] Fig.18 The present invention is the embodiment 4 of the treatment of U (VI), Fe 2+ and Fe 3+ Elemental analysis results of the products after wastewater treatment;
[0059] Fig.19 The present invention is the embodiment 4 of the treatment of U (VI), Fe 2+ and Fe 3+ Schematic diagram of the concentration of each element in the wastewater before and after treatment;
[0060] Fig. 20 is a scanning electron microscope image of the magnetotactic bacteria powder of Comparative Example 1 of the present invention;
[0061] Fig.21 The comparative example 1 of the present invention is used to treat the U(VI), Fe 2+ and Fe 3+ Schematic diagram of the concentration of each element in the wastewater before and after treatment;
[0062] Fig. 22 The magnetotactic bacteria in comparative example 2 of the present invention are directly loaded on carbon fibers to treat the U(VI) and Fe 2+ and Fe 3+ Scanning lens images of wastewater before (part a) and after treatment (part b);
[0063] Fig.23 The comparative example 2 of the present invention is used to treat the U(VI) and Fe 2+ and Fe 3+ Schematic diagram of the concentration of each element in the wastewater before and after treatment. DETAILED DESCRIPTION
[0064] In order to make the technical solution of the present invention clearer, the present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0065] The carbon fiber used in the embodiment of the present invention is a hydrophilic carbon fiber, 200g / m 2 , air permeability <55%, purchased from Kunshan Shangte New Materials Co., Ltd., the scanning electron microscope test of hydrophilic carbon fiber is as follows Figure 2 shown.
[0066] Example 1
[0067] like Figure 3-Figure 4 As shown, prepare the biological material containing magnetotactic bacteria:
[0068] S1 pickling: immerse 4 sheets of 85mm╳85mm carbon fibers in 2.5wt% nitric acid solution, ultrasonically clean for 25min, take out, first clean with 5wt% NaOH aqueous solution until neutral, then clean three times with deionized water, and dry at 60℃.
[0069] Prepare nutrient solution:
[0070] The specific ingredients are as follows: sodium lactate (60wt%) 4.5g / L, ammonium chloride 0.8g / L, dipotassium hydrogen phosphate 1.0g / L, magnesium sulfate heptahydrate 0.2g / L, yeast powder 0.2g / L, sodium thioglycolate 0.1g / L, mineral element mixture 1mL, pH=6.9.
[0071] The components of the mineral element mixture are: 15g / L nitrilotriacetic acid, 30g / L magnesium sulfate, 5g / L manganese sulfate, 10g / L sodium chloride, 1g / L ferrous sulfate, 1.8g / L cobalt sulfate, 1g / L calcium chloride, 1.8g / L zinc sulfate, 0.1g / L copper sulfate, 0.2g / L potassium aluminum sulfate, 0.1g / L boric acid, 0.1g / L sodium molybdate, 0.25g / L nickel chloride and 0.003g / L sodium selenite.
[0072] S2 Deposition of nutrient salt layer: Soak the dried carbon fiber in 1L nutrient salt solution, sterilize at 121°C for 30min, take it out after soaking for 24 hours, wash it three times with deionized water and freeze-dry it.
[0073] S3 Tannic Acid-Fe 3+Layer self-assembly: Add the carbon fiber with the nutrient salt layer to 500 mL of deionized water, then add 5 mL of 50 mg / mL tannic acid solution and 2 mL of 10 mg / mL FeCl3·6H2O solution, and adjust the pH to 6.5-7.0. Place in an ultrasonic cleaner for 10 minutes at 50 Hz to allow the -OH of the tannic acid to react with the Fe 3+ Self-assembled and chelated on the surface of carbon fiber to form Fe 3+ Tannic acid network structure, take out the carbon fiber, and wash it 5 times to remove the excess tannic acid and Fe 3+ Then, freeze-dried.
[0074] S4 loaded with magnetotactic bacteria: self-assembled Fe 3+ -The carbon fiber with tannic acid layer was placed in 1L of medium containing magnetotactic bacteria and inoculated with 5 (v / v)% of magnetotactic bacteria for 10 6 -10 7 The seed solution of 100 μg / mL was cultured at 30°C and 100 rpm / min for 24 h to obtain the biological material containing magnetotactic bacteria.
[0075] The selected magnetotactic bacteria is Magnetospirillum gryphiswaldense (No.: DSM 6361): the components of the culture medium are: sodium lactate (60wt%) 2.25g / L, ammonium chloride 0.4g / L, dipotassium phosphate 0.5g / L, magnesium sulfate heptahydrate 0.1g / L, yeast powder 0.1g / L, sodium thioglycolate 0.05g / L, mineral element mixture 0.5mL, pH=6.9, sterilized at 121℃ for 30min. The components of the mineral element mixture are: 15g / L nitrilotriacetic acid, 30g / L magnesium sulfate, 5g / L manganese sulfate, 10g / L sodium chloride, 1g / L ferrous sulfate, 1.8g / L cobalt sulfate, 1g / L calcium chloride, 1.8g / L zinc sulfate, 0.1g / L copper sulfate, 0.2g / L potassium aluminum sulfate, 0.1g / L boric acid, 0.1g / L sodium molybdate, 0.25g / L nickel chloride and 0.003g / L sodium selenite.
[0076] Uranium wastewater removal device:
[0077] The biological material containing magnetotactic bacteria prepared in Example 1 was installed on a uranium-containing wastewater removal device. Figure 6-Figure 7As shown, the uranium-containing wastewater removal device has an appearance of a cubic container, with an upper end and a lower end, the end close to the ground is the upper end, and the end away from the ground is the upper end; a containing space is enclosed; the biological material containing magnetotactic bacteria is located in the container and divides the containing space into two vertical parts; a supporting net is located on both sides of the biological material containing magnetotactic bacteria; the biological material containing magnetotactic bacteria is supported to divide the containing space into two parts; a water inlet is arranged on one side of the part into which the containing space is divided, close to the lower end; a water outlet is arranged on the other side of the part into which the containing space is divided, close to the upper end.
[0078] Example 2
[0079] like Figure 5-Figure 7 As shown in the figure, the water inlet of the uranium wastewater removal device equipped with the biological material containing magnetotactic bacteria prepared in Example 1 is introduced into a liquid containing U(VI), Fe 2+ and Fe 3+ The hydraulic retention time of the wastewater is 12h, and the U(VI), Fe 2+ and Fe 3+ The concentration of Fig.11 shown.
[0080] The details are as follows:
[0081] The first stage (0-24h) contains 20 µMFe in the influent 3+ , 20µMFe 2+ , 30µMU(VI), the removal rate of U(VI) in this stage reached 97.89±0.35%.
[0082] Second stage (36-60h), 30 µMFe 3+ , 30µMFe 2+ , 40µMU(VI), the removal rate of U(VI) in this stage reached 98.68±0.66%.
[0083] Phase III (72-96h), 40 µMFe 3+ , 40µMFe 2+ , 50µMU(VI), the removal rate of U(VI) in this stage reached 98.34±0.11%.
[0084] Stage 4 (108-132h) 50 µMFe 3+ , 50µMFe 2+ , 60µMU(VI), the removal rate of U(VI) in this stage reached 98.56±0.1%.
[0085] Scanning electron micrographs of biomaterials containing magnetotactic bacteria before and after treatment Figure 8As shown. Figure 8 In part a (before treatment) and part b (after treatment), it can be seen that substances are deposited on the carbon fibers. Fig. 9 This is a transmission electron microscope image of the sedimentary product, indicating that minerals have been generated. The sedimentary product was subjected to elemental analysis test, such as Fig.10 As shown, the elemental analysis test results show that the generated minerals are mainly composed of P, Fe and U, of which the U content is 32.23% and the Fe content is 11.68%, proving that the biomaterial containing magnetotactic bacteria can effectively fix Fe and U.
[0086] Example 3
[0087] The water inlet of the uranium wastewater removal device equipped with the biomaterial containing magnetotactic bacteria prepared in Example 1 was passed through a stream containing U(VI), Fe 2+ and Fe 3+ The hydraulic retention time of the wastewater is 12h, and the U(VI), Fe 2+ and Fe 3+ The concentration of Fig.15 shown.
[0088] The details are as follows:
[0089] The first stage (0-24h) contains 20µMFe in the influent 3+ , 20µMFe 2+ , 30µMU(VI), the removal rate of U(VI) in this stage reached 97.88±0.3%.
[0090] Second stage (36-60h), 20µMFe 3+ , 30µMFe 2+ , 40µMU(VI), the removal rate of U(VI) in this stage reached 96.33±0.13%.
[0091] Phase III (72-96h), 20µMFe 3+ , 40µMFe 2+ , 50µMU(VI), the removal rate of U(VI) in this stage reached 92.81±0.11%.
[0092] Stage 4 (108-132h) 20µMFe 3+ , 50µMFe 2+ , 60µMU(VI), the removal rate of U(VI) in this stage reached 91.62±0.17%.
[0093] Scanning electron micrographs of biomaterials containing magnetotactic bacteria before and after treatment Fig.12 As shown. Fig.12In part a (before treatment) and part b (after treatment), it can be seen that substances are deposited on the carbon fibers. Fig.13 This is a transmission electron microscope image of the sedimentary product, indicating that minerals have been generated. The sedimentary product was subjected to elemental analysis and the results are as follows Fig.14 As shown in the figure, the elemental analysis test results show that the generated minerals are mainly composed of P, Fe and U, of which the U content is 21.48% and the Fe content is 22.08%, proving that the biomaterial containing magnetotactic bacteria can effectively fix Fe and U.
[0094] Example 4
[0095] The water inlet of the uranium wastewater removal device equipped with the biomaterial containing magnetotactic bacteria prepared in Example 1 was passed through a stream containing U(VI), Fe 2+ and Fe 3+ The hydraulic retention time of the wastewater is 12h, and the U(VI), Fe 2+ and Fe 3+ The concentration of Fig.19 shown.
[0096] The details are as follows:
[0097] The first stage (0-24h) contains 20µMFe in the influent 3+ , 20µMFe 2+ , 30µMU(VI), the removal rate of U(VI) in this stage reached 98.47±0.48%.
[0098] Second stage (36-60h), 20µMFe 3+ , 20µMFe 2+ , 40µMU(VI), the removal rate of U(VI) in this stage reached 91.43±0.19%.
[0099] Phase III (72-96h), 20µMFe 3+ , 20µMFe 2+ , 50µMU(VI), the removal rate of U(VI) in this stage reached 78.95±0.56%.
[0100] Stage 4 (108-132h) 20µMFe 3+ , 20µMFe 2+ , 60µMU(VI), the removal rate of U(VI) in this stage reached 89.26±0.4%.
[0101] Scanning electron micrographs of biomaterials containing magnetotactic bacteria before and after treatment Fig.16 As shown. Fig.16In part a (before treatment) and part b (after treatment), it can be seen that substances are deposited on the carbon fibers. Fig.17 This is a transmission electron microscope image of the sedimentary product, indicating that minerals have been generated. The sedimentary product was subjected to elemental analysis and the results are as follows Fig.18 As shown in the figure, the elemental analysis test results show that the generated minerals are mainly composed of P, Fe and U, of which the U content is 36.67% and the Fe content is 5.7%, proving that the biomaterial containing magnetotactic bacteria can effectively fix Fe and U.
[0102] Comparative Example 1
[0103] 3 g of magnetotactic bacterial powder (not loaded on carbon fiber, scanning electron microscopy image as shown in the figure) was directly added. Fig. 20 The uranium wastewater was treated with magnetotactic bacteria powder directly. 2+ and Fe 3+ The hydraulic retention time of the wastewater is 12h, and the U(VI), Fe 2+ and Fe 3+ The concentration of Fig.21 shown.
[0104] The details are as follows:
[0105] The first stage (0-24h) contains 20µMFe in the influent 3+ , 20µMFe 2+ , 30µMU(VI), the removal rate of U(VI) in this stage reached 73.55±0.54%.
[0106] Phase 2 (36-60h), 30µMFe 3+ , 30µMFe 2+ , 40µMU(VI), the removal rate of U(VI) in this stage reached 12.95±1.1%.
[0107] Phase III (72-96h), 40µMFe 3+ , 40µMFe 2+ , 50µMU(VI), the removal rate of U(VI) in this stage reached 7.25±0.87%.
[0108] Stage 4 (108-132h) 50µMFe 3+ , 50µMFe 2+ , 60µMU(VI), and the removal rate of U(VI) in this stage reached 4.68±0.5%.
[0109] When U(VI), Fe 2+ and Fe3+ When the concentration is the same as that in Example 2, the removal efficiency of U(VI) in each stage is significantly lower than that in Example 2.
[0110] Comparative Example 2
[0111] The untreated carbon fiber raw material was placed in a culture medium containing magnetotactic bacteria and inoculated with 5 (v / v)% of magnetotactic bacteria for 10 6 -10 7 The seed solution was prepared by culturing at 30°C and 100 rpm / min for 24 h to obtain magnetotactic bacteria directly loaded on carbon fibers.
[0112] The obtained magnetotactic bacteria were directly loaded on carbon fibers instead of biological materials containing magnetotactic bacteria and installed in a uranium wastewater removal device. 2+ and Fe 3+ The hydraulic retention time of the wastewater is 12h, and the U(VI), Fe 2+ and Fe 3+ The concentration of Fig.23 shown.
[0113] The details are as follows:
[0114] The first stage (0-24h) contains 20µMFe in the influent 3+ , 20µMFe 2+ , 30µMU(VI), the removal rate of U(VI) in this stage reached 80.54±0.18%.
[0115] Phase 2 (36-60h), 30µMFe 3+ , 30µMFe 2+ , 40µMU(VI), the removal rate of U(VI) in this stage reached 59.04±1.32%.
[0116] Phase III (72-96h), 40µMFe 3+ , 40µMFe 2+ , 50µMU(VI), the removal rate of U(VI) in this stage reached 23.87±0.55%.
[0117] Stage 4 (108-132h) 50µMFe 3+ , 50µMFe 2+ , 60µMU(VI), the removal rate of U(VI) in this stage reached 19.72±1.36%.
[0118] When U(VI), Fe 2+ and Fe 3+When the concentration is the same as that in Example 2, the removal efficiency of U(VI) at each stage is significantly lower than that in Example 2. Scanning electron micrographs of magnetotactic bacteria directly loaded on carbon fibers before (part a) and after (part b) treatment are shown in Figure 2. Fig. 22 As shown. Figure 8 , Fig.12 and Fig.16 It can be seen that compared with the biomaterial containing magnetotactic bacteria, when magnetotactic bacteria are directly loaded on carbon fiber, the number of loaded magnetotactic bacteria is greatly reduced. This shows that the surface of carbon fiber is deposited with nutrients and tannic acid-Fe 3+ After the layer self-assembly treatment, the loading amount of magnetotactic bacteria on the carbon fiber can be increased, and the magnetotactic bacteria are not easily lost during the treatment of uranium wastewater, and can grow on it, thereby improving the removal effect of U(VI).
[0119] Compared with Comparative Examples 1-2, Examples 1-4 fully demonstrate that magnetotactic bacteria can be loaded on a layer of nutrient salts and tannic acid-Fe 3+ Self-assembly treated carbon fibers can greatly improve the removal efficiency of magnetotactic bacteria in iron-containing environments.
[0120] Compared with Examples 3-4, Example 2 shows that Fe 2+ and Fe 3+ When the concentration of Fe is lower than that of U(VI), the removal rate of U(VI) by magnetotactic bacteria will be affected. 3+ When the concentration of is lower than that of U(VI), the removal rate of U(VI) by magnetotactic bacteria is less affected. This is because the tannic acid-Fe 3+ The layer provides magnetotactic bacteria with the lack of Fe 3+ ion.
[0121] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A biomaterial containing magnetotactic bacteria, characterized in that: include: Magnetotactic bacteria, wherein the magnetotactic bacteria is Magnetospirillum gryphiswaldense DSM6361; A carrier for fixing the magnetotactic bacteria; A nutrient salt layer is deposited on the surface of the carrier to provide nutrients for the magnetotactic bacteria; Tannic acid-Fe 3+ layer, attached to the surface of the nutrient salt layer.
2. The biological material containing magnetotactic bacteria according to claim 1, characterized in that: The support includes hydrophilic carbon fibers.
3. A method for preparing a biological material containing magnetotactic bacteria, characterized in that: The following steps are involved: S1 acid washing: the carrier is soaked in an acid solution for washing, washed with an alkaline aqueous solution until neutral, then washed with water, and dried; S2 deposition of nutrient salt layer: soak the cleaned carrier in nutrient salt liquid, sterilize, soak for 20-28 hours, take out, wash with water, and dry; S3 Tannic Acid-Fe 3+ Layer self-assembly: Deposition of nutrient carriers, water, tannic acid and Fe 3+ The solutions were mixed, the pH of the mixed solution was adjusted to 6.5-7.5, ultrasonically reacted for 10-20 min, washed with water, and dried; S4 loading magnetotactic bacteria: mixing the carrier treated in step S3 with a culture medium containing magnetotactic bacteria Magnetospirillum gryphiswaldense DSM6361, culturing, and obtaining the biomaterial containing magnetotactic bacteria as described in any one of claims 1 to 2.
4. The method for preparing a biological material containing magnetotactic bacteria according to claim 3, characterized in that: In the step S1, the acid solution is a 2-3 wt% nitric acid aqueous solution; the cleaning is ultrasonic cleaning for 20-30 min; and the alkaline aqueous solution is a 2-8 wt% sodium hydroxide aqueous solution.
5. The method for preparing a biological material containing magnetotactic bacteria according to claim 3, characterized in that: In step S2, the nutrient salts include: sodium lactate, ammonium chloride, dipotassium hydrogen phosphate, magnesium sulfate, yeast powder, sodium thioglycolate, and a mixed solution of mineral elements; the mixed solution of mineral elements includes: nitrilotriacetic acid, magnesium sulfate, manganese sulfate, sodium chloride, ferrous sulfate, cobalt sulfate, calcium chloride, zinc sulfate, copper sulfate, potassium aluminum sulfate, boric acid, sodium molybdate, nickel chloride, and sodium selenite.
6. The method for preparing a biological material containing magnetotactic bacteria according to claim 3, characterized in that: In the step S2, the sterilization is performed at a temperature of 115-125° C. for 20-40 min.
7. The method for preparing a biological material containing magnetotactic bacteria according to claim 3, characterized in that: In step S3, the mass of the carrier: the volume of water: the mass of tannic acid: Fe 3+ The mass ratio is 4-6 g:500 mL:0.2-0.3 g:3-5 mg.
8. The method for preparing a biological material containing magnetotactic bacteria according to claim 3, characterized in that: In step S4, the culture medium containing the magnetotactic bacteria Magnetospirillum gryphiswaldense DSM6361 is inoculated with 3-7% of the magnetotactic bacteria 10 6 -10 7 / mL of seed solution; culture at 20-35℃, 80-140rpm / min for 20-28 h.
9. A uranium wastewater removal device, characterized in that: The invention comprises a biological material containing magnetotactic bacteria prepared by the preparation method according to any one of claims 3 to 8.
10. A uranium wastewater removal device according to claim 9, characterized in that: include: The container has an upper end and a lower end, the end close to the ground is the upper end, and the end away from the ground is the lower end; the container is enclosed to form a containing space; A biological material containing magnetotactic bacteria is located in the container and divides the containing space into two vertical parts; A supporting net is located on both sides of the biological material containing magnetotactic bacteria; the supporting net divides the containing space into two parts by the biological material containing magnetotactic bacteria; A water inlet is provided on one side of the part into which the accommodation space is divided, close to the lower end; The water outlet is arranged on one side close to the upper end of the other part into which the accommodating space is divided.